Current smoking in pregnant women in five geographical areas of China: a cross-sectional survey. (October 2016) - Xu, Xianglong; Rao, Yunshuang; Deng, Sha; Liu, Sheng; Guo, Jeff J; Sharma, Manoj; Zhao, Yong
Abstract: Background: Smoking during pregnancy is related to many adverse outcomes on infants. Smoking during pregnancy can cause abortion, premature birth, stillbirth, increased sudden infant death risk, and low birthweight. The aim of this study was to probe the differences in smoking among pregnant women with diverse characteristics. Methods: In this cross-sectional study, 2345 pregnant women aged 18 years and older were surveyed in person by investigators from June 1, to Aug 31, 2015, from 16 hospitals in five provinces of Mainland China (Chongqing, Chengdu, Zunyi, Liaocheng, and Tianjin). The information included demographic and economic characteristics, smoking status (pregnant women, husband, father-in-law, mother-in-law, father, mother, colleague, friend, relative). We excluded women with serious complications and cognitive disorders. All participants gave their informed consent for inclusion before they participated in the study. The study protocol was approved by the Ethics Committee of Chongqing Medical University (record number 2015008). Findings: 2345 pregnant women were included for this study, including 1755 (75%) women with first pregnancy. The mean age of the participants was 28·12 years (SD 4·13). 90 [4%] of the 2345 pregnant women smoked (for 74% of those it was their first pregnancy and for 26% their second pregnancy). 67 (74%) of the 90 smokers were aged 26–35 years, 74 (82%) had higher education level (senior college and university or above), 69 (77%) were from urban regions, and 46 (51%) were smoking during the third trimester of pregnancy. Among the 2345 participants, 939 (40%) had a husband who smoked, 719 (31%) a father-in-law who smoked, 42 (2%) a mother-in-law who smoked, 700 (30%) a father who smoked, 18 (1%) a mother who smoked, 736 (31%) at least one close colleague who smoked, 732 (31%) had at least a friend who smoked, and 625 (27%) had at least a relative who smoked. Compared with pregnant women of basic education level, those of higher education level (senior college and university or above) were positively associated with the risk of smoking (OR 4·98, 95% CI 1·94–12·80). Compared with pregnant women living in rural areas, pregnant women living in urban areas were inversely associated with the risk of smoking (0·55, 0·33–0·94). Compared with pregnant women whose mother-in-law did not smoke, those whose mother-in-law smoked were positively associated with the risk of smoking (4·61, 1·86–11·44). Interpretation: Tailored intervention programmes to reduce smoking in pregnant women should focus on women of higher education level, living in rural areas, and women whose mother-in-law smoke. Funding: This project was supported by theMedjaden Academy & Research Foundation for Young Scientists (MJR20150047 ). This study was also funded by Summer Social Practice Project of School of Public Health and Management, Chongqing Medical University.